2010
DOI: 10.1123/jtpe.29.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Instructional Determinants of Student Engagement in Physical Education

Abstract: This study was conducted to identify student characteristics and instructional factors that impact student engagement in physical education (PE). Data were derived from the systematic observation of 124 sessions taught by 31 physical educators and the administration of health and PE engagement questionnaires to 2,018 students in grades 5–8. Physical activity was directly affected by student engagement and perceived competence in PE and indirectly affected by students’ body image through its association with PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 45 publications
(56 reference statements)
1
20
0
2
Order By: Relevance
“…Competition is highly emphasized by high levels of traditional game play. This leads to a competitive environment and has been found to alienate less-skilled students (Bevans et al, 2010). Unfortunately, in a performance climate, only limited students receive positive feedback (Dweck, 1986), and the focus is on competition and viewing mistakes as failures (Ames, 1992).…”
Section: The Climatementioning
confidence: 99%
“…Competition is highly emphasized by high levels of traditional game play. This leads to a competitive environment and has been found to alienate less-skilled students (Bevans et al, 2010). Unfortunately, in a performance climate, only limited students receive positive feedback (Dweck, 1986), and the focus is on competition and viewing mistakes as failures (Ames, 1992).…”
Section: The Climatementioning
confidence: 99%
“…With respect to the topic of the PE course, previous research (e.g., Fairclough & Stratton, 2005) has shown that MVPA levels are generally greater during fitness-oriented activities and team invasion games (e.g., basketball and soccer) when compared with net games (e.g., badminton) and movement activities (e.g., dance and gymnastics). In addition, depending on the specific topic of the PE course, some classes are likely to display more engaged behavior than other classes (Bevans et al, 2010).…”
Section: Examining Class-to-class Variation In Physical Activity and mentioning
confidence: 99%
“…Students' interpersonal differences in motivation may relate to variation in their physical activity levels during the PE course (Cox, Smith & Williams, 2008;Ntoumanis, 2001). In addition, motivation may also vary from one class to another as a function of factors such as the gender distribution within the class (Lyu & Gill, 2011;Olafson, 2002), the topic of the lesson (Bevans, Fitzpatrick, Sanchez, & Forrest, 2010;Hassandra, Goudas, & Chroni, 2003), the structure of the class environment (Papaioannou, Marsh, & Theodorakis, 2004), and the style of the teacher (Mouratidis, Vansteenkiste, Lens, & Sideridis, 2011). Although it is reasonable to assume that between-class differences in motivation are associated with class-to-class variation in physical activity and engagement-with some classes being more physically active and engaged than others-to our knowledge, no study in the PE context has directly examined this issue.…”
mentioning
confidence: 99%
“…Taught well, PE has the capacity to contribute to the development of, not only physical skills, but also social, emotional and cognitive skills (Bailey, 2006). When students engage in learning, they invest behavioural, affective and cognitive effort to the task (Bevans, Fitzpatrick, Sanchez & Forrest, 2010). Furthermore, engaged students can be identified by interrelated expressions of motivation such as, self-determined forms of motivation and mastery motivation (Reeve, Jang, Carrell, Jeon & Barch, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, while the experiences that are external to the school are difficult for teachers to affect, the teacher can at least attempt to have some influence on the ways that pupils experience the PE context. Indeed, research suggests that teachers can create learning environments that have a direct impact on pupil motivation and subsequent engagement in PE (Bevans et al, 2010). For example, when PE teachers create a mastery motivational climate, where success is defined through personal gain, cooperation and effort, then student engagement in PE has been found to increase (Ntoumanis, Pensgaard, Martin & Pipe, 2004).…”
Section: Introductionmentioning
confidence: 99%